Boosting Vocabulary Mastery with Quizlet: A Study on Seventh Grade Students - Munir, Fairus Suryani; Samad, Pratiwi; Abbas, Moh. Jenli (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to explore the improvement of vocabulary mastery using Quizlet. The method used is quantitative with a pre-experimental research design and data collection using tests and questionnaires. The data analysis technique used is descriptive statistics. The results of the analysis show that the difference in students before and after the application of Quizlet usage is significantly different. The average pre-test score of students in vocabulary was 43.2, rising to 78.5, with a percentage increase of 81.7%. Data collection results were calculated using SPSS. The Wilcoxon signed-rank test analysis showed that Sig. (2-tailed) = 0.00, which is less than α = 0.05. This means that there is a significant difference in students' vocabulary before and after using Quizlet.